2000
DOI: 10.1002/hep.510310134
|View full text |Cite
|
Sign up to set email alerts
|

Decreased immunogenicity of recombinant hepatitis B vaccine in chronic hepatitis C

Abstract: The immunogenicity of hepatitis B vaccine is unknown for patients with chronic hepatitis C, although hepatitis B vaccination is highly recommended in these patients. We therefore studied in a prospective open trial of 59 patients with chronic hepatitis C (mean age 42 years, hepatitis C for G10 years, Child-Pugh score I5) and 58 healthy hospital staff persons the rate of nonresponse (anti-HBs F10 mIU/mL at 9 months) to recombinant hepatitis B vaccine (Gen H-B-Vax R ,10g intradeltoidal at month 0, 1, and 6). Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
111
2
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 50 publications
9
111
2
5
Order By: Relevance
“…In one study, this reduced allostimulatory capacity was associated with reduced IFN-␥ secretion in mixed lymphocyte reaction supernatants and reduced LPS-induced IL-12-secreting capacity (32). Consistent with this impairment in allostimulatory function are the findings that HCV-infected individuals have an impaired response to new antigenic stimulation with hepatitis A, hepatitis B, and influenza vaccinations (33)(34)(35), while responses to recall Ags are unimpaired (10,13,14,36). Therefore, it appears that there is an APC-based impairment in development of T cell responses in HCV infection.…”
mentioning
confidence: 77%
“…In one study, this reduced allostimulatory capacity was associated with reduced IFN-␥ secretion in mixed lymphocyte reaction supernatants and reduced LPS-induced IL-12-secreting capacity (32). Consistent with this impairment in allostimulatory function are the findings that HCV-infected individuals have an impaired response to new antigenic stimulation with hepatitis A, hepatitis B, and influenza vaccinations (33)(34)(35), while responses to recall Ags are unimpaired (10,13,14,36). Therefore, it appears that there is an APC-based impairment in development of T cell responses in HCV infection.…”
mentioning
confidence: 77%
“…Hepatitis B vaccination is recommended for patients with chronic HCV infection (27). Among HCV-infected patients without HBV infection, the main objective is to protect them against HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that patients with hepatitis C, co-infected with HBV or HIV, had lower rates of sustained response (elimination of the virus) when treated with interferon, possibly as a consequence of interactions between these viruses. It is also known that there is less seroconversion to anti-HBs in patients with HCV who are vaccinated against HBV (27).…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study of general population in the United States of America, more than 25% of HCV patients had also hepatitis B markers -which was nearly six times higher than in the HCV-negative group [4] . Previous studies demonstrated the safety of HBV vaccine use in patients with chronic hepatitis C. Immunisations did not aggravate the course of hepatitis C and had no effect on serum HCV-RNA levels [5][6][7] . Our earlier study proved that vaccinations could be safely delivered during treatment with interferon [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the hepatitis B vaccine immunogenicity in patients with hepatitis C have yielded mixed results. Most of them (but not all) indicated a diminished response to HBV vaccine delivered in a standard dose and schedule [5][6][7][8] . In our own experience, the HBV vaccine immunogenicity in patients with hepatitis C was decreased.…”
mentioning
confidence: 99%